A Knot Not to Be Cut? The Legacy of Brexit over the CJEU - Simoncini, Marta (2021)
What was the role of the Court of Justice of the European Union (CJEU) in the Brexit saga? And what will the impact of Brexit be over the future structure and activity of the CJEU? This article deals with this twofold question and explores three different issues. Firstly, we will offer a reflection on the questions and the risks raised by the Wightman case, where the CJEU ruled on the unilateral revocation of the UK notification of its intention to withdraw from the European Union under Art. 50 Treaty of the EU. Secondly, we will analyse the impact of Brexit on the composition of the CJEU and, particularly, the risks for the independence of the Court raised by the advanced termination of the mandate of the British Advocate General. Thirdly, we will provide some insights on the scope of the jurisdiction of the CJEU in the post-Brexit Union, emphasising how the Withdrawal Agreement maintained its jurisdiction during and even beyond the transition period. This article reflects the events that took place up to 6 October 2020.